A critical review of methods used to determine phosphorus and digestible amino acid matrices when using phytase in poultry and pig diets. (2019) - Dersjant-Li, Yueming; Hruby, Milan; Evans, Ceinwen; Greiner, Ralf
Summary: Phytase is applied in animal feed based on its standard activity measured at pH 5.5, however the relative activity at pH 3 (e.g. stomach pH, the main site for the breakdown of phytate) varies among the commercial phytases, ranging from 56% (an E coli phytase) to 235% ( Buttiauxella phytase). These diverse sources of phytases have varying capability for degrading phytate and, correspondingly, different P, digestible amino acid and metabolisable energy matrix values. In addition, the matrix values recommended by different phytase suppliers are not comparable, as different methodologies have been used to determine them. Phosphorus (P) and other matrix values can be determined by direct measurement of digestible P (dP) improvements by the addition of phytase above a negative control in large numbers of in vivo studies using increasing phytase doses. Alternatively, matrix values can be assessed by indirect measurement, using inorganic P (usually mono- or dicalcium sources) as a reference, typically based on tibia or metacarpal ash as a response parameter to estimate available P equivalence, either at a single or different phytase doses. When using the indirect measurement, the available P equivalence with increasing phytase doses may be calculated based on a log linear model. Although both methods are acceptable methodologies, direct measurement may under-estimate and indirect measurement may over-estimate matrix values, and a large number of in vivo studies give the best estimates of matrix values. Phytase efficacy can be influenced by phytase source, dose level, dietary composition (Ca level and Ca: P ratio). Phytase end users are encouraged to be aware of the methods used by suppliers to determine matrix values, before applying them in their feed formulations.